Williams-Beuren Syndrome and Congenital Lobar Emphysema: Uncommon Association with Common Pathology? - Timothy Andrew Walsh; Krishna Revanna Gopagondanahalli; Atul Malhotra (Case Reports in Pediatrics)
Introduction. Congenital lobar emphysema (CLE) and Williams-Beuren Syndrome are two rare conditions that have only been reported together in a single case study. Case Presentation. We report another case of a male Caucasian newborn with nonspecific initial respiratory distress, with detection of CLE on repeat chest X-ray on Day 25 of life and concurrent ventricular septal defect, supravalvular aortic stenosis, and branch pulmonary stenosis, in whom a 7q11.23 deletion consistent with Williams-Beuren Syndrome was made. Conclusion. A diagnosis of congenital lobar emphysema should prompt further screening for congenital heart disease and genetic deletion, and further research is needed to investigate the role of elastin gene mutation in the development of the neonatal lung.